Ш.СЕЙТОВ ШЫҒАРМАЛАРЫНДА ЖЕКЕ АВТОРЛЫҚ ФРАЗЕОЛОГИЗМЛЕРДИҢ ҚОЛЛАНЫЛЫЎЫ - Саденова, Г.П. (FAN va JAMIYAT, 2023)
The article is mentioned the tool of conveying ideas in a figurative and artistic way -phraseology, authorship-individual phrases and its types. Additionally,the characteristics of the use of individual author’s phraseology are discussed in the work of well-known writer Sh.Seytov.